Fearless in Physical Activity: The Implications of Community-Based Physical Activity Interventions on Children, Adolescents, and Adults with Congenital Heart Disease - Adam Chubbs-Payne; Jenna Yaraskavitch; Lillian Lai; Jennifer Graham; Poppy DesClouds; Patricia E. Longmuir (Journal of Cardiovascular Development and Disease, 2022)
People living with CHD do less moderate-to-vigorous activity than their peers. This study sought to examine the impact of a community-based physical activity intervention for individuals with CHD. Individuals with CHD and family members participated in a 3 h, one-day Fearless event consisting of a variety of physical activity and education sessions. Consenting participants completed self-administered questionnaires pre-/post-event and completed a post-event feedback form. Descriptive statistics and paired t-tests were calculated across subgroups for each outcome/questionnaire. Written feedback was analyzed using a six-phase framework of reflexive thematic analysis. A total of 32 participants (six children, six adolescents, five youth, five all ages, and ten adults) with CHD completed this study. Following Fearless, youth with CHD reported spending less time being ‘inactive’ and more time being ‘somewhat active’. Adults with CHD reported spending more time walking and partaking in moderate activity and less time partaking in vigorous activity. Fearless successfully engaged individuals with CHD who were more sedentary, less active, and older. Fearless is a fun, family-friendly, physical activity intervention for individuals with CHD. Attending a Fearless event helped children, adolescents, and adults with CHD make incremental improvements to their physical activity levels and provided a framework for sport and recreation leaders who aim to promote physical activity amongst individuals with CHD.